Pengaruh Sikap, Norma Subjektif, Religiusitas, Pengetahuan Kewirausahaan, dan Faktor Demografi terhadap Minat Berwirausaha - Muhammad Syariful Anam; Mochlasin Mochlasin; Wina Yulianti; Iqmahanis Afisa; Niken Ayu Safitri (Jurnal Ilmu Manajemen, 2021)
This study aims to identify the influence of attitude variables, subjective norms, religiosity, entrepreneurial knowledge, and demographic factors on entrepreneurial intention. The population of this study are all active students of IAIN Salatiga. In contrast, the number of samples used was 374 students. Multiple linear regression techniques were used to analyze the data. All independent variables have a significant effect on the entrepreneurial intention simultaneously. While partially, the variables that have a positive and significant effect on entrepreneurial intention are attitudes, subjective norms, entrepreneurial knowledge, study programs, and entrepreneurial experience. While the variables of religiosity, gender, age, entrepreneurship courses, and campus organization partially have no significant effect on entrepreneurial intention. Higher education institutions should continue to encourage students to grow interested in entrepreneurship. These efforts can be made through strengthening entrepreneurship courses and entrepreneurial training.